The use of vascular homografts in pediatric small bowel transplantation: Single‐center experience over a decade. (22nd January 2018) - Kwon, Yong K.; Llore, Nathaly; Kaufman, Stuart S.; Matsumoto, Cal S.; Fishbein, Thomas M.; Girlanda, Raffaele
Abstract: Intestinal transplantation in children has evolved with more isolated small intestine transplants being performed compared to combined liver‐intestine transplants. Consequently, surgical techniques have changed, frequently requiring the use of vascular homografts of small caliber to revascularize the isolated small intestine, the impact of which on outcomes is unknown. Among 106 pediatric intestine and multivisceral transplants performed at our center since 2003, 33 recipients of an isolated small intestine graft were included in this study. Outcome parameters were thrombotic complications, graft, and patient survival. A total of 29 of 33 (87.9%) patients required arterial and/or venous homografts from the same donor, mainly iliac or carotid artery and iliac or innominate vein, respectively (donor's median age 1.1 years [2 months to 23 years], median weight 10 kg [14.7‐48.5]). Post‐transplant, there were three acute arterial homograft thromboses and one venous thrombosis resulting in two peri‐operative graft salvages and two graft losses. Three of four thromboses occurred in patients with primary hypercoagulable state, including the two graft losses. Overall, at a median of 4.1 years (1‐10.2) from transplant, 29 of 33 (88%) patients are alive with 26 of 33 (79%) functioning grafts. The procurement of intact, size‐matched donor vessels and the management of effective post‐transplant anticoagulation are critical.